Records management: a basis for organizational learning and innovation (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The understanding of (trans)formations related to organizational learning processes and knowledge recording can promote innovation. The objective of this study was to review the conceptual contributions of several studies regarding Organizational Learning and Records Management and to highlight the importance of knowledge records as an advanced management technique for the development and attainment of innovation. To accomplish this goal, an exploratory and multidisciplinary literature review was conducted. The results indicated that the identification and application of management models to represent knowledge is a challenge for organizations aiming to promote conditions for the creation and use of knowledge in order to transform it into organizational innovation. Organizations can create spaces and environments for local, regional, national, and global exchange with the strategic goal of generating and sharing knowledge, provided they know how to utilize Records Management mechanisms.Keywords: Knowledge. Organizational learning and innovation. Records management.Link para o texto completo (PDF)http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/1956/1752